Legal Regulations and Process Stages Concerning Initial Public Offerings in The Indonesian Capital Market - Nugraheni, Prasasti Dyah; Rahayu, Sang Ayu Putu (Universitas Medan Area, 2025)
This study aims to describe the legal regulations and stages of the initial public offering (IPO) process in the Indonesian capital market. This scientific article employs a normative juridical research approach, utilizing qualitative literature studies as data collection techniques. The results of this scientific article include various legal regulations in the Initial Public Offering process in the Indonesian capital market, namely Financial Services Authority Regulation Number: 41 / POJK.04 / 2020, Law Number 8 of 1995, Law Number 21 of 2011, and Law Number 4 of 2023. Various stages of the Initial Public Offering process in the Indonesian capital market, namely the document preparation and initial preparation stage, the share listing stage and application for registration of preliminary agreements on the Indonesia Stock Exchange, the stage of submitting applications for registration of preliminary agreements at the Financial Services Authority, the stage of public offering of shares on the Indonesia Stock Exchange, and the stage of trading and general listing of shares on the Indonesia Stock Exchange.